Dyslalia in the research perspective of the first 25 years of the third millennium. Theoretical and methodological foundations of original research - Konopska, Lilianna; Pluta-Wojciechowska, Danuta (Papers in Linguistics, 2025)
The aim of this article is to present the theoretical and methodological foundations of original research on the scope, type and number of Polish scientific studies focused on the issue of phoneme realization disorders (dyslalia) which were undertaken in the years 2000–2024. This study presents preliminary research results, i.e. the main and detailed categories of the research area concerning dyslalia-like speech disorders and the types of scientific articles and their number based on the methodological framework of the literature review.